Bet‐hedgers commit to the hedge: Zooplankton in ephemeral semiarid wetlands of tropical Brazil that widely spread risk. Issue 5 (20th March 2023) - Pires, Mateus M.; Vendramin, Daiane; Medeiros, Elvio S. F.; Stenert, Cristina; Batzer, Darold P.; Maltchik, Leonardo
Abstract: Bet‐hedging is an ecological risk‐aversion strategy in which a population does not commit all its effort toward a single reproductive event or specific environmental condition, and instead spreads the risk to include multiple reproductive events or conditions. For aquatic invertebrates in dry wetlands, this often takes the form of some propagules hatching in the first available flood, while remaining propagules hatch in subsequent floods (the "hedge"); this better ensures that a subset of propagules will hatch in a flood of sufficient duration to successfully complete development. Harsh environmental conditions are believed to promote an increased reliance on bet‐hedging. Bet‐hedging studies have typically been restricted to single sites or single populations. Community‐level assessments may provide more robust support for the range of hatching strategies that exist in nature. Here, we tested whether freshwater zooplankton assemblages inhabiting ephemeral and unpredictable wetlands of a semiarid zone of tropical Brazil employ hatching strategies suggestive of bet‐hedging; few efforts have addressed bet‐hedging in the tropics where the unique conditions may influence the strategy. We collected dry sediments from six ephemeral wetlands, and flooded them across a sequence of three hydrations under similar laboratory conditions to assess whether hatching patterns conform to some of the predictions of the bet‐hedging theory. We found that taxa showing hatching patterns akin to bet‐hedging associated with delayed hatching numerically dominated the assemblages that emerged from dry sediments, although there was large heterogeneity in the hatching rate among sites and across taxa. While some populations distributed their hatching across all three floods and committed most of their hatching fraction to the first hydration, others committed as much or more effort to the second hydration (the "hedge") or the third hydration (another substantial "hedge"). Thus, in the harsh study wetlands, hatching patterns akin to bet‐hedging associated with delayed hatching were common and occurred at multiple temporal scales. Our community assessment found that a commitment to the "hedge" was greater than the current theory would predict. Our findings have broader implications; bet‐hedger taxa seem especially well equipped to tolerate stress if conditions become harsher as environments change.